WAYS OF TEACHING FOLKLORE SAMPLES IN MOTHER TONGUE AND READING LITERACY LESSONS IN PRIMARY GRADES (International journal of artificial intelligence, 2025)
This article highlights the use of samples of folk oral creativity—such as proverbs, fables, idioms, fairy tales, and wise sayings—in the teaching of primary school lessons. It discusses how these forms of folklore contribute to developing students’ linguistic competence, enriching their vocabulary, and enhancing their ability to form new words and express themselves effectively.